Aspiration in Baling Malay - Mohammad Khairulanwar Abdul Ghan; Mohd Tarmizi Hasrah (Nusa, 2023)
In this study, we provide all available information on the presence of aspirated voiceless stops in Baling Malay. In addition to presenting relevant lexical data, we discuss the underlying origin and phonological processes of its formation. This study employed a qualitative approach and the data were scrutinized using a descriptive linguistic method. A cross-dialect comparison shows that the formation of aspirations in Baling Malay is a locational phenomenon, finding close parallels in other languages in the northern Malay Peninsula resulting from omnipresent contact with Thai and Patani Malay. In other words, circumstances such as boundaries, politics, and mass migration of the Patani community to Kedah between the 16th and 17th centuries indirectly resulted in linguistic contact.